Kaidah-kaidah Pemahaman Esoteris Al-Qur'an Abu al-Hasan al-Haralli - Marsyam, Abdul Waris (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2022)
Abstract: This article describes the principles of esoteric understanding of the Qur’an by Abū al-Ḥasan al-Ḥarāllī, a Moroccan sufi and Qur’anic interpreter. Lack of studies have been paid attention to al-Ḥarāllī’s hermeneutical interpretation while he has successfully formulated ten rules on esoteric understanding of the Qur’an. By using descriptive-analytical method, the article argues that al-Ḥarallī’s rules of Qur’anic interpretation is related to the principles in the tafsīr bi al-Ishārah school. Al-Ḥarāllī calls the esoteric interpretation as fahm al-Qur’ān (understanding of the Qur’an) to distinguish it from the exoteric interpretation. Of the ten principles of al-Ḥarāllī’s esoteric understanding, there are three main interrelated principles, namely (1) ma‘rifatullāh (knowing God) through His beautiful Names (asmā’ al-ḥusnā) in the Qur’an, (2) mastering the scope of the Qur’anic text, and (3) self-purification (tazkiyat al-nafs) in order to arrive at the levels of meaning of the Qur’an. Abstrak: Artikel ini mengkaji tentang kaidah-kaidah pemahaman esoterik al-Qur’an Abū Ḥasan al-Ḥarāllī, seorang sufi dan mufasir al-Qur’an asal Maroko. Tidak cukup banyak kajian akademik yang mengkaji pemahaman al-Qur’an al-Ḥarāllī, padahal dia telah merumuskan sepuluh kaidah tentang pemahaman esoterik atas al-Qur’an. Dengan menggunakan metode deskriptif-analitis, artikel ini berargumen bahwa rumusan kaidah-kaidah tafsir al-Ḥarāllī dikategorikan dalam kaidah-kaidah mazhab tafsīr bi al-Ishārah. Al-Ḥarāllī menyebut tafsir esoterik atas al-Qur’an dengan istilah fahm al-Qur’ān (pemahaman al-Qur’an) untuk membedakannya dengan tafsir eksoterik. Dari kesepuluh kaidah pemahaman esoterik al-Ḥarāllī, terdapat tiga prinsip utama yang saling berkaitan, yaitu (1) Makrifatullah (mengenal Allah) melalui asmā’ al-ḥusnā dalam al-Qur’an; (2) pengetahuan tentang cakupan teks al-Qur’an, dan (3) penyucian diri (tazkiyat al-nafs) untuk mencapai tingkatan-tingkatan makna al-Qur’an.